Redevelopment of buildings in Mumbai city: risks and challenges - Vanvari, Vinod; Sumedh Mhaske, Dr (International Journal of Engineering and Technology, 2018)
In most cities of developing countries, old buildings always tend to undergo redevelopment. There are one or more than one reasons for this. Such as buildings which are in dilapidated condition or uneconomic to repair or tenants are in a need of more usable floor area. This activity of building redevelopment is much visible in Mumbai city for past decade and half. Because of various constraints and considerations, this process of projects of building redevelopment is quite complex. It takes considerable efforts and time to accomplish the projects. If a proper and time bound process is not followed, or if the risks, uncertainties and challenges are not handled properly, even a seemingly simple project can fail, thereby causing great anguish and hardship to the stakeholders. Sometimes this may lead to prolonged litigation. Â There is a need to identify risks and challenges involved in the process of building redevelopment projects. The aim of researchers is to interact with all the stakeholders of building development projects of housing societies and identify various risks and challenges visa-a-vis gains. The study has also revealed various pitfalls and uncertainties related to these projects. This will enable concerned stakeholders to prepare to address these.